A new species in the genus Aphlugiolopsis Wang, Liu & Li, 2015 (Tettigoniidae: Meconematinae) with descriptive notes on the known species from China - Wang, Yang; Li, Yun; Shi, Fuming; Chang, Yanlin (Zootaxa, 2024)
This paper reports one new species of the genus Aphlugiolopsis Wang, Liu & Li, 2015, i.e. Aphlugiolopsis zhenfengensis sp. nov. and provides supplementary description of Aphlugiolopsis punctipennis Wang, Liu, & Li, 2015 and Aphlugiolopsis lobata Pan & Bian, 2023, the female of the latter is described for the first time.